Drinking water quality and arsenic health risk assessment in Sistan and Baluchestan, Southeastern Province, Iran. Issue 4 (19th May 2019) - Radfard, Majid; Yunesian, Masud; Nabizadeh, Ramin; Biglari, Hamed; Nazmara, Shahrokh; Hadi, Mahdi; Yousefi, Nader; Yousefi, Mahmood; Abbasnia, Abbas; Mahvi, Amir Hossein
ABSTRACT: Access to drinking water is one of the most important indicators determined by the World Health Organization (WHO). This investigation surveyed the concentration of various pollutants in drinking water and its health risk attribute to Arsenic in Sistan and Baluchistan province, Iran. Water samples were collected from ground water and analyzed for physical parameters, anions, and heavy metals using the standard procedures. The concentrations of sulfate (269 ± 127 mg/l) in five sites exceeded the permissible limit (250 mg/l), while chlorine concentrations (223 ± 100 mg/l) in four sites exceeded the permissible limit (250 mg/l) set by WHO. Similarly, the concentrations of Mg (30 ± 11 mg/l) in four sites exceeded the permissible limit (30 mg/l), while Na concentrations (222 ± 99 mg/l) in five sites exceeded the permissible limit (200 mg/l) set by Institute of Standards and Industrial Research of Iran (ISIRI). In addition, arsenic was in acceptable levels recommended by WHO and local regulations. Based on the calculated indices of hazard qutient (HR) and excess lifetime cancer risk (ELCR), the in-use drinking water has no adverse effects on the consumer's health. Excessive use of fertilizers and pesticides, unsuitable sewerage systems, and inappropriate sludge and solid waste disposal in this province can lead to drinking water pollution. Also, excessive pumping of ground water should be managed as an effective method for supply of safe drinking water.